Rational Design and Synthesis of Reversible Covalent PPARγ Antagonistic Ligands Inhibiting Ser273 Phosphorylation. Issue 9 (15th January 2019) - Kim, Hyunsoo; Jo, Ala; Choi, Sun‐Sil; Nam, Hyunsung; Byun, Wan Gi; Bae, Hwan; Choi, Jang Hyun; Park, Seung Bum
Abstract: Peroxisome proliferator‐activated receptor gamma (PPARγ) has been a major therapeutic target for the treatment of type 2 diabetes. However, the use of PPARγ‐targeting drugs such as rosiglitazone and pioglitazone has significantly declined due to adverse effects caused by their classical transcriptional agonism. Meanwhile, blocking the obesity‐induced phosphorylation of PPARγ at Ser273 by Cdk5 has been proposed as the key to developing insulin‐sensitizing effects of PPARγ‐targeting drugs. In this study, we rationally designed and synthesized selective PPARγ phosphorylation inhibitor through a crystal structure‐based approach. During this process, we observed a distinct degradation pattern of the anilinic cyanoacrylamide moiety via the spontaneous retro‐aldol reaction. Thus, we developed a novel reversible covalent inhibitor of PPARγ phosphorylation, SB1495, containing aliphatic cyano‐acrylamide, through systematic structural modification, in silico docking studies, time‐dependent monitoring of stability in aqueous media, and in vitro kinase assay. We also demonstrated its inhibitory activity on PPARγ phosphorylation without classical transactivation in a cellular system as well as in an animal model. Abstract : The other way around : A revesible covalent peroxisome proliferator‐activated receptor gamma (PPARγ) inhibitor of Ser273 phosphorylation was developed by introducing a reversible covalent cyanoacrylamide moiety. Through systematic structure modification and in silico simulations, a series of reversible covalent inhibitors with improved aqueous stability were designed and synthesized. Biological studies revealed that SB1495 inhibits the phosphorylation of PPARγ without unwanted classical transcriptional agonism.